Performance Analysis of H2O-LiBr Absorption Refrigeration Systems for Future Cars - Darwin Rio Budi Syaka; Ragil Sukarno; Jeff Michael Johanes; Gaguk Margono (Fakultas Teknik Universitas Pancasila, 2025)
There has been an increase in the development of electric cars in recent decades, driven by the global need to reduce greenhouse gas emissions and air pollution. The use of refrigeration systems in electric cars is one of the largest consumptions of electric power. Therefore, this study used an absorption refrigeration system with a working fluid in the form of a combination of water as a refrigerant and lithium bromide salt as an absorption compound (H2O-LiBr) as an alternative refrigeration system.However, the use of water as a refrigerant leads to the required components being larger. This study focuses on analyzing the work performance of absorption refrigeration systems. The results of the analysis of the performance of the absorption refrigeration system state that to get the optimal performance value in operating the designed H2O-LiBr absorption refrigeration system, the generator outlet temperature is required to be a minimum of 75°C, which produces a performance stated in COP of 0.705. In the meantime, the analysis of the generator outlet temperature's impact on the refrigeration system's performance value revealed that the higher the generator outlet temperature, the higher the performance value.